A Ponder & Sedulousness Of Legion Shale Stabilizing Materials In Aqueous Based Drilling Fluid During The Process Of Borehole Strengthening - M Panbarasan; Dr.S.Venkateshbabu; R.Karthikeswaran; J.Sudharsan (International Journal of Pollution: Prevention & Control, 2024)
Drilling fluid used while drilling the layers of shale will have the potential of reacting with water which tends to increase stickiness, induce swelling and promote sloughing of the borehole. This results in the reduction of drilling fluid circulation, increased mud loss, increase in torque and drag, reduction in lubricity. This will ultimately result in the increase of Non-Productive Time (NPT) during drilling which in turn increases Capital Expenditure (CAPEX) to the operators thus leads to the longer return on investment (ROI) thereby directly impact the project economics. The drilling fluids which also mixes with the aquifers and it leads to subsurface deformation and environment pollution. Now the pollution control boards are using stringent measures to curb the pollution either on or below the surface, any driller fail to comply has to pay a hefty sum as penalty or else leads to banning in operation. This can be overcome by adding shale stabilizing agents to the drilling fluid. But shale stabilizing agents can reacts differently with the type of formations and depth at which it is used. Various physical properties such as appearance, bulk density, pH, moisture content, water solubility, solubility in oil, sulphonate group, thermal stability, particle size, fluid loss, strain has to be considered and their reactivity with numerous types of shale rock with its different petrophysical properties such as permeability, water saturation, shale volume, wettability, porosity, pore volume compressibility, relative permeability, capillary pressure, oil saturation and water saturation has to be taken into account. In this paper, various shale stabilizing agents are added with water-based drilling muds which was employed in different subsurface formations and its’ behaviour was studied.
Keywords: Borehole; Drill Cuttings; Drilling fluid; Filter press; Fluid loss; Mud loss; Shale stabilizer